2021
DOI: 10.1080/15438627.2021.1888108
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and modelling the game speed outputs of English Championship soccer players

Abstract: This study aims to quantify and model the game-speed demands of professional soccer players competing in the English Championship league, to compare the effect of match location and to examine the effect of playing position on game-speed outputs across the season. Twenty-eight male professional soccer players were enrolled. Moving average calculations were applied to the raw GNSS (STATSports) speed data of each player's duration matches (home = 14 and away = 9). Positional groups were centre-back (CB), full-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…The differences reported in match demands in this study should be also considered when developing the physical qualities needed to progress from U18 to the U23 and 1ST teams. Sports scientists need to monitor the training and match loads of their players to balance and plan appropriate physical stimuli during training sessions (Vanrenterghem et al, 2017;Connor et al, 2021). Several researchers reported that the match represents the most important physical stimulus of the week and plays a key role in achieving long-term physical development (Anderson et al, 2016;Morgans et al, 2018;Gualtieri et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The differences reported in match demands in this study should be also considered when developing the physical qualities needed to progress from U18 to the U23 and 1ST teams. Sports scientists need to monitor the training and match loads of their players to balance and plan appropriate physical stimuli during training sessions (Vanrenterghem et al, 2017;Connor et al, 2021). Several researchers reported that the match represents the most important physical stimulus of the week and plays a key role in achieving long-term physical development (Anderson et al, 2016;Morgans et al, 2018;Gualtieri et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The League is often used as a pre-season competition, whereas the Championship is considered the most important, with the All-Ireland final viewed as one of the biggest sporting events of the year in Ireland [5]. The match-play running demands of hurlers have previously been reported [1,[6][7][8]. However, no research has differentiated between the two elite senior hurling competitions.…”
Section: Introductionmentioning
confidence: 99%
“…These GPS technologies have been shown to provide valid and reliable measures of running performance in team sports [10,11]. Several studies have reported the match-play running performances in soccer [12][13][14][15], rugby [16][17][18], Gaelic football [19,20], field hockey [21,22], and hurling [1,[6][7][8]23] using GPS. Specifically, the total distance, distance per minute, distance covered at high-speed running (HSR) and sprinting, the number and length of sprints, and the peak speeds have been quantified [1,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations